A novel ERAP2 haplotype structure in a Chilean population: implications for ERAP2 protein expression and preeclampsia risk. Issue 2 (30th May 2013) - Vanhille, Derek L.; Hill, Lori D.; Hilliard, DaShaunda D.; Lee, Eun D.; Teves, Maria E.; Srinivas, Sindhu; Kusanovic, Juan P.; Gomez, Ricardo; Stratikos, Efstratios; Elovitz, Michal A.; Romero, Roberto; Strauss, Jerome F.
Abstract Single nucleotide polymorphisms (SNPs) in the endoplasmic reticulum aminopeptidase 2 (ERAP2) gene are associated with preeclampsia (PE) in different populations. rs2549782, a coding variant (N392K) that significantly affects substrate specificity, is in linkage disequilibrium (LD) with rs2248374, a marker SNP associated with ERAP2 protein expression in previously studied populations. As a result of nonsense‐mediated RNA decay, ERAP2 protein is not expressed from the rs2248374 G allele. We previously reported that the fetal rs2549782 minor G allele is associated with PE in African‐Americans, but not in Chileans. In this study, we found that rs2549782 was in LD with rs2248374 in African‐Americans, but not in Chileans. The unexpected lack of strong LD in Chileans raised the possibility that rs2248374 could be associated with PE in the absence of an association with rs2549782. However, we found no significant association for this allele with PE in Chileans. Chileans homozygous for the rs2248374 G allele did not express 110 kDa ERAP2 protein, consistent with nonsense‐mediated RNA decay, and carriers of the rs2248374 A allele did. We conclude that the Chilean ERAP2 haplotype structure allows for the expression of the major T allele of rs2549782 encoding 392N, which could impact peptide trimming and antigen presentation. Our discovery of racial differences in genetic structure and association with PE reveal heretofore unrecognized complexity of the ERAP2 locus.